Climate of doubt - Hockenberry, John.; Low, John E.; Upin, Catherine; Documentary Group (New York, N.Y.); PBS Distribution (Firm).; Public Broadcasting Service (U.S.).; WGBH (Television station : Boston, Mass.) ([Arlington, Va.] PBS : Distributed by PBS Distribution, 2012)
Four years ago, climate change was hot. Politicians from both parties, pressed by an anxious public, seemed poised to act. But that was then. Today, public opinion about the climate issue has cooled, and politicians either ignore the issue or loudly proclaim their skepticism of scientific evidence that human activity is imperiling the planet. What?s behind this reversal? FRONTLINE goes inside the organizations that fought the scientific establishment to shift the direction of the climate debate
Climate rebels -- From consensus to "Climategate" -- A new reality on Capitol Hill -- Beyond Washington -- "Money well spent"
"Frontline is a production of WGBH/Boston..."
Documentary
Director of photography, Tim Grucza ; editor, Chad Ervin ; production associate and researcher, Brian Taylor ; music, John E. Low
Correspondent, John Hockenberry
DVD; NTSC, Region 1; widescreen presentation; stereo
English subtitles for the deaf and hard of hearing (SDH)
Keywords: Climatic changes -- Government policy -- United States; Climatic changes -- Political aspects -- United States; United States -- Politics and government -- 21st century